Private law and power - Barker, Kit (Portland, Oregon : Hart Publishing, 2017)
The aim of this edited collection of essays is to examine the relationship between private law and power - both the public power of the state and the 'private' power of institutions and individuals. It describes and critically assesses the way that private law doctrines, institutions, processes and rules express, moderate, facilitate and control relationships of power. The various chapters of this work examine the dynamics of the relationship between private law and power from a number of different perspectives - historical, theoretical, doctrinal and comparative. They have been commissioned from leading experts in the field of private law, from several different Commonwealth Jurisdictions (Australia, the UK, Canada and New Zealand), each with expertise in the particular sphere of their contribution. They aim to illuminate the past and assist in resolving some contemporary, difficult legal issues relating to the shape, scope and content of private law and its difficult relationship with power
Part 1: Issues -- 1. The Dynamics of Private Law and Power -- Kit Barker -- Part 2: Power, History and Society -- 2. Power, History and the Law of Contract in Eighteenth Century England -- Warren Swain -- 3. Redressing Inequality in Personal Credit Transactions: 1700-1974 -- Karen Fairweather -- 4. Tort Law and Government Liability in the Administrative State -- Peter Cane -- Part 3: Doctrines, Institutions and Process -- 5. Property and Power: The Judicial Redistribution of Proprietary Rights -- Craig Rotherham -- 6. Trustees' Powers and Social Justice -- Matthew Harding -- 7. Undue Infl uence and the Spiritual Economy -- Simone Degeling -- 8. A Public Law Tort: Understanding Misfeasance in Public Office -- Donal Nolan -- 9. Public Power, Discretion and the Duty of Care -- Kit Barker -- 10. The Legitimacy of the Company as a Source of (Private) Power -- Ross Grantham -- 11. Reshaping Responsibility: The Emerging Private Law of Institutional Wrongs -- Mayo Moran -- 12. Class Actions: Uses and Abuses of the Process of Courts -- Justice Philip McMurdo
Includes bibliographical references and index.
Also issued in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Electronic reproduction.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Civil law -- Commonwealth countries; Power (Philosophy); Power (Social sciences); Public law -- Commonwealth countries